SEPARATION BETWEEN SPOUSES, DUE TO DEFECTS A COMPARATIVE STUDY BETWEEN JURISPRUDENCE AND THE LAW OF IRAQ AND THE ARAB COUNTRIES - Mohamed Abed Hamoodi Al-Ameri; Ahmed Nazim Al-Zaidi; Dr. Mahbouba Mina (Scholar Express Journals, 2022)
In this research, we dealt with the issue of differentiation of defects between spouses and the details and merits it included, and it became clear to us that jurisprudence and laws, especially the Arabic ones, are in agreement, even if in a general way, on the right of the spouses to request a differentiation because of faults and defects. Some laws consider the defect a reason for the termination of the contract from its foundation, as did some jurisprudential opinions. Legislation also relied on medical reports and expert opinion in defining the ailments and defects and their duration, and the laws gave sufficient respite for the defects that are subject to demise, in an attempt to restore the opportunity to build the family entity that is threatened with demise. And in another reference within the research, most of the legislations did not specify specific reasons to make them stable, so they gave the reasons, for example, to make the law more flexible in dealing with bugs and defects, and it also gave the judge the authority to rely on medical reports and experts to decide on those newly developed ailments . We have devoted the first topic in this research with two demands to define the differentiation of defects linguistically and idiomatically, and we dealt with in the second section the annulment of the marriage contract for the defect in the perspective of Muslim jurists with three demands that dealt with the subject in detail. Iraqi law and the laws of Arab countries.
Keywords: Spouses; Laws; Muslim jurists